Urban Planning Approach and Production of Counter Architecture: A Case Study of New Market, Khulna - Raihan Khan; Apurba K. Podder (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Informal spatial practices in cities of the Global South are often regarded as activities taking place outside the realm of regulatory oversight. The prevailing urban governance and planning paradigms, which are largely derived from developed countries, struggle to adapt to the dynamic nature of these practices and the inherent conflicts they entail. Furthermore, the influence of disorderly political systems further complicates matters at the local level. In response to planned development, informal spatial practices persist as a critical yet overlooked/integral aspect of ever-evolving urban realities. This paper provides new insights into the current dynamics surrounding the creation of informal urban spaces in Global South cities and their interaction with the formal planning framework. Our study focused on the city of Khulna in Bangladesh, a compelling case study with a history of failed industrial planning dating back to the 1960s, when it was designed by a group of British consultants. Following its initial failure and the city’s subsequent decline in population, Khulna has witnessed an unforeseen surge in ‘counter spatial’ development driven by the imperative to meet socio-economic and cultural needs. This paper underscores the significance of such type of informal spatial production and introduces/highlights the concept of ‘counter architecture’ as a pivotal element of society that demands recognition and inclusion in the broader urban development framework. It suggests that the ‘counter architecture’ lens provides a foundation for challenging the rigidity of master planning and understanding the interconnectedness between formal and informal urban spaces. This perspective emphasizes the need to consider the lived experiences and tactical attributes of spatial formation, ultimately highlighting the resistance of ‘inhabitants’ and ‘users’ against the static codes of modern master planning in cities of Global South like Khulna.